MiRNAs as Potential Biomarkers for Traumatic Brain Injury: Pathway From Diagnosis to Neurorehabilitation. Issue 3 (May 2021) - Herrold, Amy A.; Kletzel, Sandra L.; Foecking, Eileen M.; Saban, Karen L.; Przybycien–Szymanska, Magdalena M.; Zilliox, Michael; Bhaumik, Dulal; Lange, Dustin; Radke, Jay R.; Salinas, Ilse; Bender Pape, Theresa L.
Abstract : Background: Biomarkers that can advance precision neurorehabilitation of the traumatic brain injury (TBI) are needed. MicroRNAs (miRNAs) have biological properties that could make them well suited for playing key roles in differential diagnoses and prognoses and informing likelihood of responsiveness to specific treatments. Objective: To review the evidence of miRNA alterations after TBI and evaluate the state of science relative to potential neurorehabilitation applications of TBI-specific miRNAs. Methods: This scoping review includes 57 animal and human studies evaluating miRNAs after TBI. PubMed, Scopus, and Google Scholar search engines were used. Results: Gold standard analytic steps for miRNA biomarker assessment are presented. Published studies evaluating the evidence for miRNAs as potential biomarkers for TBI diagnosis, severity, natural recovery, and treatment-induced outcomes were reviewed including statistical evaluation. Growing evidence for specific miRNAs, including miR21, as TBI biomarkers is presented. Conclusions: There is evidence of differential miRNA expression in TBI in both human and animal models; however, gaps need to be filled in terms of replication using rigorous, standardized methods to isolate a consistent set of miRNA changes. Longitudinal studies in TBI are needed to understand how miRNAs could be implemented as biomarkers in clinical practice. Abstract : Supplemental Digital Content is Available in the Text.